Biaxial Stretching of Polymer Nanocomposites: A Mini-Review - Chen, Xiaoyu; Xiang, Dong; Zhou, Zuoxin; Wu, Yuanpeng; Li, Hui; Zhao, Chunxia; Li, Yuntao (Frontiers in Materials, 2021)
Abstract: Polymer nanocomposites with excellent physical and chemical properties and multifunctional performance have been widely used in various fields. Biaxial stretching is not only an advanced film manufacturing process, but also a deformation mode in other processing methods such as blow film extrusion and thermoforming. In recent research, high-performance polymer nanocomposites have been fabricated via sequential and simultaneous biaxial stretching. This fabrication method enhances the mechanical properties, optical performance, and thermal properties of polymer nanocomposites by changing the structure or orientation of materials during the process of stretching. Therefore, it is particularly suitable for use in optimizing material performance and preparing thin films with excellent properties in the packaging industry. With the emergence of new materials and technologies, polymer nanocomposites prepared by biaxial stretching have demonstrated multifunctional properties and their range of applications has further expanded. In this mini-review, the effect of biaxial stretching on the structure and properties of nanocomposites based on various nanofillers is discussed and applications are summarized. In addition, the challenges and future prospects of this technology are analyzed. The presented work will be beneficial for improving preparation processes and improving future research for the production of high-performance polymer nanocomposites.